Geochronological and mineralizing fluid constraints associated with the Washita Valley Fault System - Rickert, James Kenneth Phillips (My University, 2025)
The Arbuckle Mountains, Oklahoma, correspond to an inverted aulacogen uplifted during the Pennsylvanian (320-290 Ma). The Arbuckle Mountains are affected by a large-scale strike-slip fault system: the Pennsylvanian Washita Valley Fault System. Based on stable (O, C) and radiogenic Strontium isotope approaches on carbonate rocks and veins, previous studies have attempted to resolve the syn-tectonic diagenetic and paleo fluid-flow history of the Arbuckle Mountains. Results from these studies suggest that the diagenetic alteration of carbonate exposed within the Arbuckle Mountains was dominated by meteoric fluid structurally channelized along fault systems. Although the principal tectonic phase is linked to the Pennsylvanian Arbuckle Orogeny, two other deformation events have been documented on the field, suggesting a long lasting and complicated tectonic history, opening debate about the exact timing of the sinistral Washita Valley Fault System and its related paleo-fluid flow. To resolve the exact timing of the Washita Valley Fault System activity, we performed detailed field-based structural analysis coupled with in-situ U-Pb analyses on fault related carbonate veins. In addition, we used conventional O and C stable, and [Delta]47 clumped isotope analyses on carbonate veins and their direct host rocks to document the associated fluid-related alteration. Our preliminary results suggest that the Washita Valley Fault was active during Early Cretaceous (140-109 Ma), contradicting previously proposed Pennsylvanian ages (320-290 Ma) estimated by either stratigraphic correlation or from seismic data interpretation. In addition, our new stable isotope data also suggest that the Washita Valley Fault System acted as an open hydrological fluid system involving marine and meteoric water at 44-68 ˚C during its activity.
Keywords: Structural geology; Arbuckle Mountains; Washita Valley Fault System; Geology